Platos típicos y turismo gastronómico del Recinto La Envidia cantón Babahoyo - Arbelay Moreira, Karina Sofía (2022)
The present case study is based on research related to our professional profile, Typical Dishes and Gastronomic Tourism of the En vida Del Babahoyo Canton Campus, which aims to raise awareness among future and current generations to preserve their customs, ideas and gastronomy related in the field. Tourist. Therefore, it is necessary to engage the cultures that still keep their customs, maintain a kind of appreciation and make their young people aware of how important it is to create places or develop tourism and whose purpose is to demonstrate the great variety of economy that exists in the equator. The methodology that is going to be used within the research is qualitative, using techniques such as surveys that are directed to the people who live around these tourist places and the interviews are directed to the owners of these places to obtain truthful information for the development of the case study